2012
DOI: 10.1152/japplphysiol.01432.2011
|View full text |Cite
|
Sign up to set email alerts
|

Atelectrauma disrupts pulmonary epithelial barrier integrity and alters the distribution of tight junction proteins ZO-1 and claudin 4

Abstract: Mechanical ventilation inevitably exposes the delicate tissues of the airways and alveoli to abnormal mechanical stresses that can induce pulmonary edema and exacerbate conditions such as acute respiratory distress syndrome. The goal of our research is to characterize the cellular trauma caused by the transient abnormal fluid mechanical stresses that arise when air is forced into a liquid-occluded airway (i.e., atelectrauma). Using a fluid-filled, parallel-plate flow chamber to model the "airway reopening" pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…Similarly, in vitro models of mechanical ventilation, whereby cell monolayers are stretched at physiologically relevant magnitudes, have revealed that large stretch levels increase permeability, typically measured as a flux of radio-labeled or fluorescently tagged macromolecules from apical to basal sides of the cell monolayer (18, 19, 30) or transport of charged tracers measured via increased transepithelial/endothelial electrical resistance (TER) across the cell monolayer (9, 12, 26, 28). Given the paucity of permeable and distensible cell monolayer substrate materials, recently we reported permeability measurement whereby BODIPY-tagged ouabain (BO) in the apical media is able to bind to basolateral Na+-K+ ATPase pumps on epithelial cells that are only accessible when tight junction barrier properties are compromised (Figure 1A) (8, 11, 12, 14-16, 22, 37). This method is specific to epithelial cells, and is sensitive to the stretch-induced variation in the number of Na+-K+ ATPase pumps on the cell membrane (14).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in vitro models of mechanical ventilation, whereby cell monolayers are stretched at physiologically relevant magnitudes, have revealed that large stretch levels increase permeability, typically measured as a flux of radio-labeled or fluorescently tagged macromolecules from apical to basal sides of the cell monolayer (18, 19, 30) or transport of charged tracers measured via increased transepithelial/endothelial electrical resistance (TER) across the cell monolayer (9, 12, 26, 28). Given the paucity of permeable and distensible cell monolayer substrate materials, recently we reported permeability measurement whereby BODIPY-tagged ouabain (BO) in the apical media is able to bind to basolateral Na+-K+ ATPase pumps on epithelial cells that are only accessible when tight junction barrier properties are compromised (Figure 1A) (8, 11, 12, 14-16, 22, 37). This method is specific to epithelial cells, and is sensitive to the stretch-induced variation in the number of Na+-K+ ATPase pumps on the cell membrane (14).…”
Section: Introductionmentioning
confidence: 99%
“…The pulmonary endothelium plays a critical role in maintaining a cellular barrier between the vascular space and the pulmonary interstitium, with biochemical or mechanical barrier-disrupting agents producing increased lung fluid flux and alveolar flooding, a hallmark of ALI (Dudek and Garcia, 2001). Mechanical ventilation can exacerbate lung injury via both excessive alveolar stretch (volutrauma) (Amato et al, 1998; Lionetti et al, 2005) and repetitive stretch of non-aerated lung units, a process known as atelectrauma (Jacob and Gaver, 2012; Yalcin et al, 2009). Ventilator-induced lung injury (VILI) results from excessive mechanical stress during mechanical ventilation (Dos Santos and Slutsky, 2000) which produces alveolar and vascular damage leading to multiple organ dysfunction (ARDSNET2000; dos Santos and Slutsky, 2000), a syndrome involving systemic effects of locally produced pro-inflammatory cytokines (Dreyfuss and Saumon, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…ZO-1 is a tight junction-associated transmembrane protein of the cytoskeleton and it may function by transducing regulatory signals that control the paracellular barrier [20,21]. Our positive ZO-1 immunohistochemistry staining results indicated that tight connections were formed between cells after the implantation of the tissue-engineered conduit, demonstrating that the cells form an intact layer of epithelium rather than single arranged cells.…”
Section: Discussionmentioning
confidence: 71%